A Fiqh Analysis of Parental Responsibility in Protecting Children from Online Game Addiction and Negative Content - Arifin, A Zaenal; Azis, Abdul; Rofiqi, Rofiqi; Al-Mohannadi, Ahmed; Nasrullah, Achmad Muzammil Alfan (STAI Publisistik Thawalib Jakarta, 2026)
This study examines the widespread involvement of children and adolescents in Mekarsari Village in unproductive mobile phone activities, such as excessive gaming and exposure to harmful content. The study aims to explore the strategies parents employ to teach about honesty, the consequences of their actions, the responsible use of technology, and the provision of religious guidance. A phenomenological approach was employed in this study. Data were collected through in-depth interviews, discussions, and observations. Data analysis encompassed the synthesis, presentation, and interpretation of findings. The study's credibility was ensured through prolonged observation, data triangulation, and confirmability. The findings indicate that parents utilize religious teachings to advise their children on limiting online gaming and avoiding harmful content. Supervision is achieved through direct communication and the internalization of religious tenets, thereby promoting the early cultivation of children's moral understanding. Children are instructed that all actions have repercussions, highlighting the importance of discipline in worship, spiritual responsibility, and the prudent incorporation of technology within educational and familial contexts. Parents utilize tawhid-based education and moral development to counteract digital addiction, guiding children toward becoming religious, wise, and responsible individuals. In conclusion, parental advice, encompassing honesty, the instruction of consequences, and religious education, is efficacious in mitigating undesirable conduct. This study underscores that a fiqh-based methodology, along with moral education, is crucial in cultivating children's character to develop into disciplined and responsible persons.